2019
DOI: 10.1021/acs.macromol.9b01349
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Styrenic Blends with Poly(lactic acid)

Abstract: Polymer pollution from nonbiodegradable polymer blends is a source of increasing environmental concern. The obvious solution, the replacement of petroleum-based polymers with biodegradable polymers from renewable sources, is difficult, since these polymers are highly immiscible. Here, we show how the addition of only a few percent of a tertiary phase can enable compatibilization and enhancement of the mechanical properties. The tertiary phase can be selected for any binary polymer system using the spreading co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…However, the mixing time for binary blends played a significant role. In accordance with the results, Zuo et al report that the addition of SMMA only slightly affects the module elastic for PLA-SMMA-PS and PLA-SMMA-high impact PS (HIPS) [36]. A possible explanation for this could be that by adding the SMMA copolymer at 0 or 10 min, preferred placement is at the interface between the EVA and PLA.…”
Section: Tensile Testssupporting
confidence: 59%
See 1 more Smart Citation
“…However, the mixing time for binary blends played a significant role. In accordance with the results, Zuo et al report that the addition of SMMA only slightly affects the module elastic for PLA-SMMA-PS and PLA-SMMA-high impact PS (HIPS) [36]. A possible explanation for this could be that by adding the SMMA copolymer at 0 or 10 min, preferred placement is at the interface between the EVA and PLA.…”
Section: Tensile Testssupporting
confidence: 59%
“…In addition, the monomeric units of styrene are miscible with EVA; and methyl methacrylate is miscible with PLA. Zuo et al reported that PLA high-impact polystyrene blends utilize SMMA as a compatibilizing agent due to their higher miscibility with PLA and HIPS [36].…”
Section: Dynamic Mechanical Thermal Analysismentioning
confidence: 99%
“…Usually, the temperature range of heating elements is kept between 170-185 o C. Blends of PLA have been often prepared to provide rigidity in which various kinds of biopolymers are added like polyethylene glycol (PEG), poly(butylene succinate) (PBS), poly(hydroxy acid) (PHA), natural rubber (NR), polycaprolactone (PCL) and poly(hydroxy butyrate) (PHB). These blends are prepared by a melt blending process in which polymers are mixed in a beaker and stirred [18]. Thereafter, the required reinforcement is added to the blend.…”
Section: Process Of Manufacturing Pla Based Compositesmentioning
confidence: 99%
“… 3 , 4 It is widely believed that these problems may be largely overcome by substituting traditional petroleum-based plastics with biopolymers derived from nature and degradable synthetic polymers. 5 , 6 Currently, poly(lactic acid) (PLA), a popular biodegradable polymer with good biocompatibility and high mechanical strength, has been widely studied and applied for this purpose. 7 9 However, the inherent brittleness and poor ductility of pure PLA limit its wide use, especially in applications where high toughness is required.…”
Section: Introductionmentioning
confidence: 99%